On the Pathogenesis of the Irritable Bowel Syndrome: The Irritable Bowel or the Irritable Patient? - Stephen M Collins (Canadian Journal of Gastroenterology)
The traditional perspective of irritable bowel syndrome (IBS) as a behavioural problem has tended to downplay the role of gastrointestinal dysfunction. Contrary to predictions based on the traditional philosophy, a recent study has shown that IBS patients have increased pain tolerance compared to healthy subjects. This profile of pain tolerance is similar to that seen in chronic organic disease of the gut (eg, Crohn's disease), raising the possibility that IBS patients may experience pain resulting from gastrointestinal dysfunction. The recent finding of increased airway responsiveness to inhaled methacholine in certain IBS patients provides an objective and quantifiable measurement of tissue dysfunction in that syndrome, and focuses attention on possible mechanisms underlying the altered responsiveness of hollow organs in patients with IBS; these mechanisms are discussed.